Sedimentation Rate Analysis in Dock C PT. Petrokimia Gresik, Indonesia - Abiyani Choirul Huda; Rendatiyarso Laksono; Anggie V R Dewi; Rima G Harahap; Nurwati Nurwati; Siti Rahayuningsih; Destyariani L Putri; Anggoronadhi Dianiswara; Muhammad K Wirawan (MO.RI Publishing, 2021)
Dock C is one of the supporting facilities at PT. Petrokimia Gresik which functions as loading and unloading goods from ships to land and vice versa. Another benefit of the jetty is that it can significantly increase the company's production capacity. Dock C PT. Petrokimia Gresik. In the treatment of sedimentation in port it is necessary to analyze the current pattern and sedimentation rate early, because this is the first step to predict the amount of sedimentation contained in the port in a certain period of time. Several ways can be done to minimize the rate of sedimentation, one of which is the layout of Dock C to reduce the frequency of dredging. This study compares the sedimentation volume at the existing condition jetty and two alternative jetty that occur due to currents and waves, while modeling is done using Mike 21. The results of the existing jetty modeling show the sedimentation volume for 12 months was 20641.68 m3. Whereas the sedimentation volume from alternative jetty 1 and 2 produced for 12 months was 11293.56 m3 and 7426.2 m3. Modifications to the layout of the jetty provided were able to reduce the rate of sedimentation in Dock C, with the most optimal sedimentation volume for 12 months at 13215.48 m3